SARS-CoV-2 - an update in virology: A Narrative Review - Mohabeer, Poornasha; Banerjee, Indrajit; Kashyap, Abishek; Shukla, Ananya; Robinson, Jared; Ramdhan, Nikhil D. (Journal of Biomedical Sciences, 2020)
Background: SARS-CoV-2 is the highly infectious new coronavirus, which has been associated with the pandemic COVID-19. The majority of those pathogenic coronaviruses are benign, namely HCoV-229E, HCoV-NL63, HCoV-OC43 and HCoV-HKU1, and they have been linked to common cases of flu. Two of these viruses namely SARS coronavirus and MERS coronavirus are known to have caused more severe infections. Based on phylogenetic analysis, the Coronaviruses are divided into four groups, which are: Alpha-CoV, Beta -CoV, Gamma-CoV, and Delta -CoV. The Beta- CoV genus is further classified into four lineages, which are referred to as Groups A, B, C, and D. At the genomic level, SARS-CoV-2 has been identified to match with the lineage B of Beta coronavirus. This infection affects the respiratory tract, mainly the lungs' alveoli, and can cause a wide variety of symptoms ranging from discharge from the nose and a sore throat to respiratory distress, septic shock, and failure of multiple organs. To date, millions of people have been affected by the virus. The current mortality rate is around 6%. Early diagnosis is essential to prevent the spread of the infection. An extensive literature review was done using Pubmed, Medline, Pubmed Central, Embase, Goggle Scholar databases from January 20, 2020, till October 20, 2020. Conclusion: COVID-19 is the third outbreak of a pathogenic human coronavirus, after MERS and SARS. Its high rate of transmissibility has taken a toll on citizens' personal and professional lives globally. The peculiarities of SARS-CoV-2, regarding its genomic uniqueness and the role of Malayan pangolins as intermediate hosts, still demands more research to determine the degree to which they partake in the generation of the pathogenicity and infectiousness of the virus.